TEKNOLOGI TOKOPEDIA PLAY LIVE SHOOPING DALAM PERSPEKTIF EKOLOGI MEDIA KONVERGENSI - mulyana, agung putra; Djamzuri, Muhammad Irfan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Communication experience designed to be a digital communication technology conveys messages without limits to the communicant. This technology can even be used as an online buying and selling transaction process such as live shopping on the Tokopedia platform. The researcher discusses the form of integration of the Tokopedia Play feature in the buying and selling process. The method used is a case study with a qualitative approach and the use of interview, observation, and documentation techniques. The results of this study can be seen that the Tokopedia Play menu is able to affect human feelings because it is displayed on the main page of the application. In terms of media convergence, Tokopedia's shopping activities are considered as a form of communication in terms of marketing and even embedded as an entertainment platform, so not only buying and selling transactions but buyers can also enjoy the content presented.